Exploring University Students' Preferences for Teacher Oral Corrective Feedback Types: Insights from Finland - Shaltaeva, Elizaveta (My University, 2024)
Students’ preferences and beliefs are essential to be considered in language teaching strategies. Since oral corrective feedback is a part of the language acquisition process in the classroom setting, students’ preferences for the strategies of oral corrective feedback that they receive on their speech from their teachers. The purpose of this research is to explore these preferences in the Finnish university context. The objectives include examining Finnish-speaking students’ preferences for teacher oral feedback in detail and the influence of students’ background variables such as gender, proficiency level, and field of study on these preferences. Additionally, the Finnish-speaking students’ preferences are compared to the ones of non-Finnish-speaking students. Finally, the impact of students’ awareness of oral corrective feedback functions and purposes is examined. The study employs a mixed-method approach, utilising surveys for quantitative data and interviews for qualitative insights. Findings indicate that Finnish-speaking university students favour recasts the most, followed by explicit correction and metalinguistic feedback. Elicitation, repetition, and clarification requests are the least favoured feedback strategies. Despite this general trend, some students' preferences for oral corrective feedback types deviate from the observed pattern. The research also highlights a difference between male and female students, with females showing a more favourable attitude towards recasts. No significant differences in preferences are identified across proficiency levels and fields of study. While Finnish-speaking students generally share similar preferences for oral corrective feedback types as non-Finnish-speaking students, they display a more negative attitude towards clarification requests, possibly due to discomfort with being singled out. Awareness of the functions and reasons for feedback types may influence the preferences of some students, but its general impact remains inconclusive. The study suggests that recognizing individual preferences beyond the general pattern is crucial in educational practice. Additionally, classroom dynamics can be influenced by various backgrounds. Educators can enhance their feedback practices by explaining feedback goals, thereby improving students’ second language acquisition processes.
Keywords: corrective feedback, oral corrective feedback, teacher oral corrective feedback, students’ preferences, students’ beliefs, language teaching, language learning, second language acquisition